Mechanical properties of rice husk filled impact modified unplasticised poly(vinyl chloride) composite - Ahmad, Mazatusziha (2006)
Rice husk (RH) is one of the natural fillers that offer a number of advantages over inorganic fillers since they are biodegradable, low cost, recyclable and renewable. This study investigates the performance of RH as filler for unplasticised poly(vinyl chloride) (PVC-U) composites. In the sample preparation, composites with different RH loadings varied from 10 to 40 phr were prepared using two-roll mill at temperature 165 oC before being hot pressed at temperature 185 oC. Tensile, flexural and izod impact test were conducted in order to investigate the mechanical properties of the composites. Incorporation of RH fillers from 10 to 40 phr has resulted in the increased of flexural modulus indicating an improvement in stiffness. The effects of acrylic impact modifier and LICA 12 coupling agent on the mechanical properties of PVC-U composites were investigated. The acrylic impact modifiers were found to be effective in enhancing the impact strength at all levels of RH content. Effectiveness of the impact modifier in enhancing the impact strength decreased with increasing RH content. LICA 12 was found to be the most effective in increasing impact strength at 20 phr RH loading. The processability of RH filled PVC-U composites was studied by using Brabender Plasticorder. It was found that incorporation of RH has resulted in decreasing the fusion time of the PVC compounds while the heat distortion temperature (HDT) increased at all RH loadings. The degradation temperature (T10%) decreased with increasing RH content. The percentage of water absorption increased slightly with increasing RH content and treated samples exhibited lower percentage of water absorption compared to the untreated samples. The optimum composition which gives balance of properties based on stiffness and toughness of PVC-U composites is PVC-U at 8 phr of acrylic impact modifier and 20 phr of RH treated with LICA 12